2004
DOI: 10.1111/j.1745-4514.2004.06003.x
|View full text |Cite
|
Sign up to set email alerts
|

Amylase and Helicobacter Pylori Inhibition by Phenolic Extracts of Pineapple Wastes Bioprocessed by Rhizopus Oligosporus

Abstract: This study focused on the potential functional activity of phenolicenriched pineapple wastes bioprocessed by Rhizopus oligosporus . Using the phenolic-enriched bioprocessed extracts, amylase inhibition relevant to Type 2 diabetes and Helicobacter pylori inhibition linked to stomach ulcer were investigated. Two treatments were studied: 9 g of pineapple residue plus 1 g of soy flour (P9) and 5 g of pineapple residue plus 5 g of soy flour (P5). Extracts obtained after 2 and 10 days of growth were selected to repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 21 publications
0
29
0
1
Order By: Relevance
“…There is a possibility that urease bound to the outer membrane of H. pylori, which provides the ideal microenvironment for its survival under acidic pH by creating a microenvironment of ammonia (Hawtin, Stacey, & Newell, 1995) maybe inhibited similar to other phytochemicals (Lin, Kwon, Labbe, & Shetty, 2005). HPLC analysis of pineapple solid-state bioprocessed extracts by the same fungus indicates that simple and biphenyl compounds contributed to high H. pylori inhibition (Correia et al, 2004) suggesting a similar mobilization in mung bean.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…There is a possibility that urease bound to the outer membrane of H. pylori, which provides the ideal microenvironment for its survival under acidic pH by creating a microenvironment of ammonia (Hawtin, Stacey, & Newell, 1995) maybe inhibited similar to other phytochemicals (Lin, Kwon, Labbe, & Shetty, 2005). HPLC analysis of pineapple solid-state bioprocessed extracts by the same fungus indicates that simple and biphenyl compounds contributed to high H. pylori inhibition (Correia et al, 2004) suggesting a similar mobilization in mung bean.…”
Section: Resultsmentioning
confidence: 87%
“…Phenolics are usually found in conjugated forms, with one or more sugar residues bound to hydroxyl groups, or groups of compounds such as carboxylic and organic acids, amines and lipids (Bravo, 1998). Therefore in this study the potential of SSB using food-grade fungus was investigated to mobilize the conjugate forms of phenolic precursors naturally found in mung bean to improve its functionality as observed in fava bean, cranberry pomace, and pineapple (Correia, McCue, Magalhães, Macêdo, & Shetty, 2004;Randhir, Vattem, & Shetty, 2004;Vattem, Lin, Labbe, & Shetty, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…(WhWheat, BwBuckwheat, CnCorn, OtOats, SpSprouts, SdSeedlings, NANot Autoclaved, AAutoclaved). Shetty, 2004) suggesting a similar alteration to the phenolics profile due to thermal processing. Other research indicates that highly oxidized phenolic compounds are more toxic to microorganisms (Urs and Dunleavy, 1971) suggesting a likely mode of phenolic oxidation due to thermal processing.…”
Section: Resultsmentioning
confidence: 92%
“…Total phenolics were increased by two times when the fungus Rhizopus oligosporus was incubated for 12 days in 1:1 pineapple: soybean flour mixture. Another bioprocess where mixture of pineapple residue and soy flour (9:1 and 5:5) using R. oligosporus has revealed that extracts obtained after 2 days with 9:1 treatment showed potent á-amylase inhibition while the extract obtained after 10 days with 5:5 treatment exhibited Helicobacter pylori inhibition (Correia et al, 2004b). They have linked these activities with the phenolic compounds present in the system.…”
Section: Utilization Of Pineapple Wastementioning
confidence: 99%